Regionalistics of Ukraine - Balak, Ilona O. (Lesya Ukrainka Volyn National University, 2023)
The academic component "Regionalistics of Ukraine" studies and explains the basic processes and phenomena of economic life of the region covers the question of functioning of cooperation between a state and the regions at the present stage of the development. An important place in the course structure is the analysis of historical preconditions, structural parts of regional economy, state regulation of regional economy, different regions of Ukraine peculiarities. The publication outlines the thematic structure of the lecture materials, presents questions for seminar classes and test tasks for self-assessment, and a list of recommended references. It is recommended for students of 2nd year for the bachelor’s degree preparation, specialty 291 «International Relations, Public Communication and Regional Studies», educational and professional program «International Relations»
Keywords: region; international relations; 332.1=111